2015
DOI: 10.17113/ftb.53.02.15.3582
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Tomato Powder Fermented with Pediococcus pentosaceus and Lactobacillus sakei for the Ready-to-Cook Minced Meat Product Quality Improvement

Abstract: SummaryIn this study, the infl uence of lactic acid fermentation on the quality of tomato powder was evaluated. The eff ect of adding fermented tomato powder to ready-to-cook minced pork meat to improve its nutritional value and sensory characteristics was also analysed. The cell growth of Lactobacillus sakei (7.53 log CFU/g) was more intense in the medium containing tomato powder, compared to the growth of Pediococcus pentosaceus (6.35 log CFU/g) during 24 h of fermentation; however, higher acidity (pH=4.1) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
0
16
2
Order By: Relevance
“…Measuring the colour of food products has been used as an indirect measure of other quality attributes, such as flavour and pigment contents, because it is simple, fast and correlates well with other physicochemical properties [100]. We found that fermentation influenced the colour characteristics and carotenoid content of tomato products ( Figure 6) [95].…”
Section: Colour Parameter Relation With Carotenoid Content In Fermentmentioning
confidence: 85%
See 4 more Smart Citations
“…Measuring the colour of food products has been used as an indirect measure of other quality attributes, such as flavour and pigment contents, because it is simple, fast and correlates well with other physicochemical properties [100]. We found that fermentation influenced the colour characteristics and carotenoid content of tomato products ( Figure 6) [95].…”
Section: Colour Parameter Relation With Carotenoid Content In Fermentmentioning
confidence: 85%
“…The influence of lactic acid fermentation with BLIS-producing lactobacilli (Pediococcus pentosaceus KTU05-9, Lactobacillus sakei KTU05-6) on the parameters of tomato powder and the impact of fermented tomato products on the acceptability, colour characteristics and carotenoid content of ready-to-cook minced pork meat products (RCMP) have been investigated [95].…”
Section: The Use Of Tomato Additives Fermented With Pediococcus Pentomentioning
confidence: 99%
See 3 more Smart Citations